Chikungunya Fever with Arthralgia, Neurological Symptoms and Pneumonia: A Case Report (Bangladesh Journal of Medical Microbiology, 2026)
Presenting a case of Chikungunya viral fever, a 75-year-old male complained of fever, polyarthralgia, and no rash. Diagnostic test for CBC shows decreased platelet count and total count of WBC. The antibodies for the chikungunya test showed a positive result for the IgM antibody. Diagnosis was confirmed by RT-PCR. After treatment patient recovered from the fever. But the patient complained of severe joint and muscle pain even after one month. The patient, after a few days, developed neurological symptoms and pneumonia. HRCT and MRI of the brain confirmed the diagnosis. Antibiotic along with steroids, were started immediately after diagnosis. Patient responded very well with subsidence of fever and feeling of well-being.Bangladesh Journal of Medical Microbiology, July 2025;19 (2):154-157